Integrating Faith and Tradition: The Baralek Tuanku Ceremony in Minangkabau - Sefriyono Sefriyono; Andri Ashadi; Zulfis Zulfis (Khazanah Sosial, 2024)
This study explores the acculturation process between Islam and Minangkabau customs, focusing on the traditional Baralek Tuanku ceremony. Fieldwork was conducted at Pesantren Nurul Yakin in Padang Pariaman, employing qualitative research methods, including observations, interviews, and participation in ceremonies. Data were analysed using thematic and narrative analysis. The study reveals that the acculturation of Islam and Minangkabau customs through Baralek Tuanku occurs in two forms: First, before the conferment of the Tuanku title, where Minangkabau values are institutionalised in the education of the students, particularly through teaching rundiang. Second, during the conferment process, where two elements of Minangkabau customs are involved: niniak mamak (customary leaders) who bestow the customary heirloom title alongside the Tuanku title, and bako (father’s sister) who prepares traditional food for the pesantren teachers. These pesantren inherit the values of the Syattariyah Order, particularly those related to maintaining the harmony between Islam and local culture, as the pesantren are managed by figures from this tarekat. This study offers a conceptual framework for understanding how dual identities can be harmoniously integrated within a community. It enriches the theoretical discourse on acculturation by providing a successful example of cultural and religious amalgamation.